Exploring leaf hydraulic traits to predict drought tolerance of Eucalyptus clones. (7th April 2022) - Oliveira, Leonardo A; Cardoso, Amanda A; Andrade, Moab T; Pereira, Talitha S; Araújo, Wagner L; Santos, Gleison A; Damatta, Fábio M; Martins, Samuel C V
Abstract: Ongoing changes in climate, and the consequent mortality of natural and cultivated forests across the globe, highlight the urgent need to understand the plant traits associated with greater tolerance to drought. Here, we aimed at assessing key foliar traits, with a focus on the hydraulic component, that could confer a differential ability to tolerate drought in three commercial hybrids of the most important Eucalyptus species utilized in tropical silviculture: E. urophyla, E. grandis and E. camaldulensis. All genotypes exhibited similar water potential when the 90% stomatal closure (Ψ g s90 ) occurs with Ψ g s90 always preceding the start of embolism events. The drought-tolerant hybrid showed a higher leaf resistance to embolism, but the leaf hydraulic efficiency was similar among all genotypes. Other traits presented by the drought-tolerant hybrid were a higher cell wall reinforcement, lower value of osmotic potential at full turgor and greater bulk modulus of elasticity. We also identified that the leaf capacitance after the turgor loss, the ratio between cell wall thickness ( t ) and lumen breadth ( b ) ratio ( t / b ) 3, and the minimal conductance might be good proxies for screening drought-tolerant Eucalyptus genotypes. Our findings suggest that xylem resistance to embolism can be an important component of drought tolerance in Eucalyptus in addition to other traits aimed at delaying the development of high tensions in the xylem. Highlight Drought tolerance in tropical Eucalyptus hybrids encompasses a high leaf resistance to embolism and a suite of traits aimed at delaying the development of high tensions in the xylem.